Å skrive om livsmot - Anne Clancy; Rolf Thorsen (Septentrio Academic Publishing, 2020)
Concerning "livsmot" The phenomenon of 'Livsmot' can be expressed in a myriad of ways. This essay is the introductory text to a special issue in Nordisk Tidsskrift for Helseforskning that in its entirety concerns 'livsmot'. The collection of essays should be of interest to students, researchers, health professionals and others. The issue highlights and discusses different philosophical approaches that can promote our understanding of what can give us courage and hope on good and bad days, in sickness and in health. The authors in the article collection write in essay form and use examples from life and research to bring forth their understanding of the phenomenon. This text contextualizes the various articles by presenting thoughts on and interpretations of 'Livsmot'